2004
DOI: 10.1242/jeb.00901
|View full text |Cite
|
Sign up to set email alerts
|

Dogmas and controversies in the handling of nitrogenous wastes: The effect of feeding and fasting on the excretion of ammonia, urea and other nitrogenous waste products in rainbow trout

Abstract: SUMMARY Ammonia and urea are the primary forms of nitrogen excretion in teleost fish. There exists, however, a discrepancy between the sum of ammonia plus urea nitrogen and total nitrogen, indicating that `unknown' nitrogen end products may play an important role in nitrogen metabolism. The current study analysed a wide range of nitrogen end products in both fed and fasted juvenile rainbow trout. Ammonia-N (53–68%) and urea-N (6–10%) were confirmed as the most important forms of nitrogenous wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 39 publications
5
69
0
Order By: Relevance
“…In keeping with this hypothesis, the relative mRNA expression and presumably protein of all Rh isoforms in the intestine was significantly higher in fed than in fasted fish. These findings are consistent with a previous study by Kajimura and co-workers, who demonstrated that significant quantities of ammonia are lost through gastrointestinal routes in fed rainbow trout (Kajimura et al, 2004).…”
Section: The Effects Of Feeding On Nitrogen Excretionsupporting
confidence: 93%
See 1 more Smart Citation
“…In keeping with this hypothesis, the relative mRNA expression and presumably protein of all Rh isoforms in the intestine was significantly higher in fed than in fasted fish. These findings are consistent with a previous study by Kajimura and co-workers, who demonstrated that significant quantities of ammonia are lost through gastrointestinal routes in fed rainbow trout (Kajimura et al, 2004).…”
Section: The Effects Of Feeding On Nitrogen Excretionsupporting
confidence: 93%
“…In addition to playing a prominent role in digestion and nutrient absorption, the gastrointestinal tract is an important site of ammonia transport and a major contributor to post-prandial ammonia release in fish (Brown and Cameron, 1991;Kajimura et al, 2004). At present, information about gastrointestinal Rh proteins comes from a single mammalian study by Handlogten and colleagues (Handlogten et al, 2005), who demonstrated that both RhBG and RhCG mRNA and protein were prominently expressed in the proximal regions of the stomach and intestinal tract, with a trend for decreasing expression along the duodenum, jejenum, ileum and colon (Handlogten et al, 2005).…”
Section: The Effects Of Feeding On Nitrogen Excretionmentioning
confidence: 99%
“…Axler et al 1997). Ammonia nitrogen can form 53 to 69% of total nitrogen wastes in the effluent of rainbow trout farms (Kajimura et al 2004), but the ratio may increase up to 79% in some in stances (Dalsgaard & Pedersen 2011). The ratios of TAN/TN in effluents in our study were unexpectedly lower than the literature values, suggesting that nitrification of ammonia and temporal variations in the samplings most likely played a significant role, as reported previously (2008), and Aubin et al (2011).…”
Section: Effluent Characteristicssupporting
confidence: 60%
“…The ratios of TAN/TN in effluents in our study were unexpectedly lower than the literature values, suggesting that nitrification of ammonia and temporal variations in the samplings most likely played a significant role, as reported previously (2008), and Aubin et al (2011). Although urea, amino acids, and nitrogen excretion via the gills and/or skin and mucus may comprise a considerable amount of the soluble fraction of organic nitrogen (Kajimura et al 2004), both soluble and particulate fractions may reach up to 36% of TN (Foy & Rosell 1991). Because we did not determine these fractions separately, our TON values are indirectly consistent with the range of the TON/ TN ratio published by Foy & Rosell (1991).…”
Section: Effluent Characteristicssupporting
confidence: 58%
“…2). This simple approach is used by more than 70% of Aus- Kajimura et al (2004) and Dalsgaard & Pedersen (2011). Graphics are from the Integration & Application Network (ian.umces.edu/symbols/).…”
Section: Primary Treatmentmentioning
confidence: 99%